Implementation of Smartphone-Based E-Learning Modules to Enhance Understanding, Creativity, and Collaboration Among Students in Chemistry - Saiful; Paulus Hengky Abram; Sitti Aminah; Tahril; Vanny Maria A Tiwow; Ratman (Postgraduate, University of Mataram, 2026)
This study aims to test the feasibility and effectiveness of implementing smartphone-based chemistry e-modules in enhancing high school students' understanding of the material, creativity, and collaboration. The research method used is pre-experimental with a one-group pretest-posttest design. The research sample consisted of 28 tenth-grade students at SMA Negeri 1 Tinombo, selected using purposive sampling technique. Data were collected thru instruments such as material comprehension tests, creativity tests, and collaboration observation sheets. The research results show that the implemented e-module meets the validity criteria with an average of 78% and is very practical to use, with a practicality score of 84.5% for teachers and 87.78% for students. The effectiveness analysis using the N-Gain test shows an increase in material understanding of 0.71 (high category). For student creativity, the N-gain value is 0.72, and for collaboration, it is reinforced by the teacher's observation results of 87.5%. Thus, it can be concluded that the smartphone-based e-module is effective in improving the quality of chemistry learning on nanomaterial topics.